Stakeholder pressure and green innovation: Pathways to competitive advantage in Vietnamese manufacturing SMEs - Huong, Dinh Thi; Nhung, Nguyen Hong; Anh, Nguyen Hong (International Journal of Innovative Research and Scientific Studies, 2025)
This study investigates the impact of stakeholder pressure, green innovation (GI), sustainable performance (SP), and competitive advantage (CA), with a focus on AI’s moderating role between employee behavior and GI. A quantitative approach was applied, collecting multi-source data from 357 SMEs in the manufacturing sector. Structural Equation Modeling (SEM) with SmartPLS assessed variable relationships, while reliability and validity were confirmed using Cronbach’s alpha and AVE. Findings reveal that normative pressure (β = 0.308, p < 0.01) has the strongest influence on GI adoption, while supplier pressure (β = 0.083, p < 0.05) has the weakest. AI positively impacts GI (β = 0.190, p < 0.01) and moderates the effect of employee behavior on GI (β = 0.101, p < 0.01). Additionally, GI enhances SP and CA, with SP mediating the GI–CA relationship. This study contributes to the literature by highlighting AI’s role in driving GI and moderating employee behavior’s influence on GI. Practically, it underscores the need for SMEs to consider stakeholder pressure and strategically integrate AI to foster GI, enhance SP, and strengthen CA in a rapidly evolving business landscape.